Increasing the Space for Creativity and Skills Through the Introduction of Ecoprinting Techniques to Youth Groups - Anou, Kezia; Bungasalu, Benny Abraham; Sinaga, Ego Srivajawaty; Ngaderman, Hubertus; Saputrina, Truly Theresia (Jurnal Pengabdian UntukMu NegeRI, 2024)
The ecoprint coloring technique has been widely applied by people from various circles because it uses natural materials that are easy to obtain and do not pollute the environment. Ecoprint is one of the batik making activities through a process of transferring color and shape to fabric through direct contact to produce environmentally friendly products. The partners for this activity are students from the Puldama district, Yahukimo Regency who are studying in Sentani, Jayapura Regency. This Ecoprint training activity is motivated by the condition of partners who do not receive enough training so that they often spend time without any useful activities being carried out. This activity consists of two stages, namely preparation and implementation. The methods used are lectures and mentoring. The results that have been achieved are that participants have knowledge about how to create works of art in the form of printed motifs on fabric using the ecoprint technique, participants have the skills to print motifs on fabric using the ecoprint technique. Participants showed an enthusiastic attitude to continue these skills as an initial form of entrepreneurship.